Analisis Gaya Bahasa Guru Bagi Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen - Jerahmel Seo; Dominggus Selan; Maglon Banamtuan (Institut Agama Kristen Negeri Kupang, 2022)
This research aims to analyze the teacher's language style for students' interest in learning about Christian religious education at the Inpres Oenoah Elementary School. The method used in this research is qualitative research, to be analyzed by means of data reduction, data presentation, and data conclusion. The data sources in this study were 6 people at the Inpres Oenoah Elementary School using the results of observations and interview guidelines. So the results obtained during the study were the relationship between the teacher's style of language for students' interest in learning, according to the results of observations and interview guidelines that in teaching Christian religious education teachers often used high language styles in the learning process, however, in learning teachers used high language to motivate students in learning so that students are not easily inclined to follow Christian religious education learning.